DEVELOPMENT OF TOURISM ROUTES FOR TEMPLES AND BUDDHIST SITES ALONG THE MEKONG RIVER IN THE MUNICIPALITY OF NAI MUEANG SUBDISTRICT, MUEANG DISTRICT, NONG KHAI PROVINCE - Panyavaro (Sunon), Phramaha Prayad; Abhivaddhano ((Tawpanthu), Phramaha Prateep; Bhuridatto (Anontree), Phra Wanchai; Munyapho, Jesada; Phuttajorn, Apiwatchai (Journal of MCU Nakhondhat, 2022)
The objectives of this research article were; to study the history of temples and Buddhist sites along the Mekong River; to survey the temples and Buddhist sites along the Mekong River; to develop a tourist route along the Mekong River for temples and Buddhist sites. This is a qualitative study that collected data by reviewing a textbook, performing a field survey, observation, and depth interviews. The key informants are the abbot of the temples and focus on 13 temples along the Mekong River in Nongkhai Municipality. Collected data will be analyzed, classified, and concluded for presenting descriptive data. As a result of this research, the 13 temples have long histories that involve the King and the communities with some of them being built and restored by the Kings of Lanchang, and others by the communities, the Buddha’s statues, and antiquities belong to Lanchang Arts, most of them were built in the reign of King Setthathirath. A survey of tourist attractions along the Mekong River, which includes famous Buddha statues such as Phra Sai, Phra Suk, Phra Sao, and Phra Saeng, as well as architectural and artistic attractions, such as Ubosoth, Vihar, Cheti, wall paintings, and temple scenes, etc. The guideline for the development of tourist routes along the Mekong River are as follows, choosing and mapping the temples and Buddhist sites along the Mekong River, setting up a database and website named “Watrimkhong Nongkhai”, printing an informational poster of temples and distribute a guidebook, brochure to the temples and State agencies that are concerned.